Low fasting methionine concentration as a novel risk factor for recurrent venous thrombosis - Keijzer, Miranda B. A. J.; den Heijer, Martin; Borm, George F.; Blom, Henk J.; Vollset, Stein Emil; Hermus, Ad R. M. M.; Ueland, Per M. (Thrombosis and Haemostasis, 2006)
Hyperhomocysteinemia is a risk factor for venous thrombosis, but the underlying mechanism is unclear. If the thiol-group of homocysteine interferes with components of the clotting system, we expect that high cysteine will be alsoa risk factor for venous thrombosis. If high homocysteine reflects a disturbed methyl-group donation by S-adenosylmethionine, we expect that low methionine will be a risk factor for thrombosis. We performeda case-control study in 185 patients with recurrent venous thrombosis and in 500 control subjects.We determined methionine, homocysteine, cysteine and assessed the associated thrombotic risk. Low fasting methionine was associated with an increased risk on recurrent venous thrombosis [ORbottom vs. top quartile = 3.3 (95%CI 1.9–5.7)]. Low methionine remained a risk factor [ORbottom vs. top quartile= 3.5 (95%CI 2.0–6.0)] after adjusting for homocysteine and cysteine, whereas the thrombotic risk for homocysteine was lost [OR= 1.0 (95%CI 0.6–1.9)] after adjustment. Cysteine yielded a highest odds ratio of 2.1top vs. bottom quartile (95%CI 1.0–4.0) after adjustment. In conclusion, we found that low fasting methionine is a risk factor for recurrent venous thrombosis.This risk association was stronger for methionine than for homocysteine or cysteine.This supports the hypothesis that impaired methylation may be involved in the pathogenesis of venous thrombosis.
Keywords: Methionine; homocysteine; cysteine; venous thrombosis